Treatment providers' perspectives on a gender-responsive approach in alcohol and drug treatment for women in Belgium - Schamp, Julie; Vanderplasschen, Wouter; Meulewaeter, Florien (Frontiers in Psychiatry, 2022)
Background Gender inequity is a pervasive challenge to health equity on a global scale, and research shows the impact of sex and gender on substance use regarding for example epidemiology, treatment needs, treatment admission and treatment outcomes. The gender-transformative approach to action and health indicates that health interventions may maintain, exacerbate or reduce gender-related health inequalities, depending on the degree and quality of gender-responsiveness within the programme or policy. However, research shows a lack of gender-responsive initiatives in the alcohol and drug addiction field. Aims The purpose of this study is to explore in depth how alcohol and drug treatment can be made more sensitive to female users' treatment needs from the perspective of service providers. Consequently, study findings can inform the development of gender-responsive treatment options and aid to a deeper understanding of how these trends are designated on the continuum of approaches to action and health in the alcohol and drug field. Methods Four focus groups were organized across different regions in Belgium with a total of 43 participants, including service providers, policy makers and women who use(d) drugs. Results The perspective of the participants on substance use prevention and treatment for female users incorporates some crucial gender-specific and gender-transformative features. Next to implementing mother-child options, a holistic approach, experts by experience and empowering women in treatment, professionals report the relevance of awareness raising campaigns targeting all levels and sectors in society. Also, recurring attention was given to the role of men in the narratives of female users. Conclusion Study findings show that the field of alcohol and drug prevention and treatment is being looked at through the lens of gender-responsiveness. However, to achieve improvement in the lives of both women and men, and hence creating more equal chances and opportunities in substance abuse treatment, the gender-transformative approach in addiction care needs to be further explored, criticized and established in practice and future research.